On Beyond Bugs! - Rabe, Tish; Ruiz, Aristides (New York : Random House, 1999)
Rhyming text and illustrations depict the Cat in the Hat and his friends exploring the many different kinds of insects, their characteristics, and behavior.
Includes bibliographical references (p. 43) and index.
Keywords: Insects -- Juvenile literature; Insects